GAYA KEPEMIMPINAN DALAM MANAJEMEN KELAS GURU PADA SISWA DI SEKOLAH DASAR DALAM MENINGKATKAN PRODUKTIVITAS PEMBELAJARAN - Adilah Salsabila; Nana Asmi Aziz; Hendri Marhadi; Mahmud Alpusari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explain and analyze the characteristics of leadership in classroom management as a teacher in a primary school class in Pekanbaru. This study employs a qualitative approach with a single-case study design, exploring a teacher’s experiences and skills in leading and managing the class through both formal and informal interactions. Data were collected through in-depth interviews, brief observations, and documentation, then analyzed via data reduction, data display, and conclusion drawing. The results show that classroom management, with the teacher positioning among students in this primary school, forms a differentiation between in-group and out-group clusters, influenced by competence, loyalty, and the deliberative (musyawarah) culture at school. This dynamic positively impacts coordination effectiveness and motivation of the in-group teachers, yet it also creates potential jealousy among the out-group.